O efeito de alginatos incorporados à ração sobre o desempenho produtivo e manejo de juvenis de tilápia do Nilo - Leonhardt, Julio Hermann; Leonhardt, Creusa Maria Rodrigues; Cericato, Leonardo [UNESP]; Zanolo, Rodrigo (Universidade Estadual de Londrina, 2011)
The alginic acid is extracted from seaweed and when used in fsh ration may induce immunomodulatory and immunostimulants responses. This study aimed to evaluate the effect of alginic acid incorporated in the ration on performance and handling of juvenile Nile tilapia, Oreochromis niloticus. The frst phase of the experiment occurred in two excavated ponds earth. 57,000 juveniles were used for Nile tilapia, local strains with the average weight of 14 grams. The juvenile Nile tilapia received the experimental diet treated with ergosan at a dose of 1% of the diet. The survival rate of fsh and feed conversion in the experimental Nile tilapia was higher than the control Nile tilapia. In the second stage 54,126 juveniles with average weight 40.63 grams, were used. These fsh were transferred to 16 fsh cages. There were no signifcant differences in mortality rate between treatments. The highest mortality occurred between the third and seventh days after the handling. The data confrm that the transfer of juvenile Nile tilapia in the ponds to fsh cages is a strong stressor. © Pleiades Publishing, Ltd., 2011.
The effect of alginate incorporated in the ration on performance and handling of juvenile Nile tilapia Silage
Keywords: Ergosan; Fish cages; Oreochromis niloticus; Stress